Contemporary Family Lifestyles in Central and Western Europe Selected Cases - Kraus, Blahoslav; Stašová, Leona; Junová, Iva (SpringerBriefs in Sociology, 2020)
This open access book brings together a unique set of comparative data from Western and Central Europe on how contemporary families live, and discusses the similarities and differences in family lifestyles in this region. The empirical data comes from the authors' original research derived from adult representatives of families with children in the Czech Republic, Germany, Latvia, Poland, Slovakia and Ukraine. The authors compare and interpret information on the social and economic situation of families, expressed satisfaction in their lifestyles, and leisure and media in the everyday life of families. Overall, the authors bring into the discussion both current knowledge and original empirical data on families and contribute to literature on the sociology of the family, particularly in Europe. This book is useful to researchers and students interested in family issues, along with professionals in the field of family care and social policy.